A rare case of perivascular epithelioid cell tumor (PEComa) of the greater omentum - Okamoto, Koichi (World J Surg Oncol, 2018)
BACKGROUND: A tumor composed exclusively or predominantly of human melanin black 45 (HMB45)-positive epithelioid cells is called a perivascular epithelioid cell tumor (PEComa). We report a very rare case of a PEComa of the greater omentum. CASE PRESENTATION: MRI conducted to examine the orthopedic disease of the patients, a 49-year-old Japanese woman, also identified a tumor in her pelvis. A CT scan revealed a tumor mass on the right side of the pelvic floor and clear nutrient vessels originating from the splenic and celiac arteries. An omental primary tumor or accessory spleen was thus suspected, and tumor resection was performed. The tumor was a light brown solid tumor with a smooth margin, measuring 5.2 × 3.8 × 3.5 cm. Histopathologically, the tumor was composed mainly of spindle and epithelioid cells, and large and small blood vessel formation was observed. In the immunohistochemical staining, tumor cells were positive for human melanin black 45 (HMB-45) and Melan-A and partially positive for alpha-smooth muscle actin. The final diagnosis was PEComa of the greater omentum. CONCLUSIONS: Although omental PEComa is very rare, it should be considered as a differential disease of an omental primary tumor.